Comparative and correlational analysis of the performance from 2016 crossfit games high-level athletes - Barbieri, João Francisco; Correia, Renan Felipe; Castaño, Luz Albany Arcila; Brasil, Douglas Vinicius Carvalho; Ribeiro, Alex Natalino (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: CrossFit is a functional training modality created by Greg Glassman in 1995 in the United States. Such modality is characterized by the execution of complex and high intensity movements with the purpose of preparing the participant for the unpredictable. It is observed the exponential increase in CrossFit practice across the world, with this increase there are a consolidation of this modality with as a very peculiar sport modality, since as tasks to be performed in the competitions are made public just before the events happen. Few studies have focused on the determinants of competitive success in CrossFit, both morphologically and performance. Objective: This present study dedicated to investigate, in the existing literature and in the results of the 2016 championship, variables that can be predicted the performance of these athletes. Methods: The performance of 40 2016 - CrossFit Games finalists of both genders were analyzed in the morphological variables (weight, height, body mass index), performance and specific tests (Benchmarks and 1 MR tests). Results: We found that among male athletes, it was not possible to identify variables that could predict a classification. However, among the women, we identified some variables that correlated with classification, such as the Benchmark Filth 50, Sprint performance of 400m and maximal loads in the Clean and Jerk and Snatch exercises. Conclusion: It was attributed to the correlations found among women the smaller participation in the Games, this allowed physical characteristics as force to influence in the final position.